A Competitive Advantage Strategy Through The Use Of Technology Marketing Information, And Orientation Of Learning With Performance As An Intervening Variable - Saimin; Lustono; D. Utami, Ristianawati (Universitas Teknologi Yogyakarta, 2020)
This study aims to determine the significance of the positive influence of marketing information technology, learning orientation, and performance on competitive advantage, to determine the significance of the positive influence of marketing information technology and learning orientation on performance, and to determine the effect of the use of information technology and learning orientation on competitive advantage through performance as an intervening variable. This research uses quantitative methods. Research variables consist of information technology, learning orientation, performance, and competitive advantage. The population in the study is all Small and Medium Enterprises (MSME) Pottery entrepreneurs in Kasongan, Bantul Regency. The sampling method is purposive sampling, based on the characteristics or criteria of the sample size of 60 respondents. The data collection method uses a questionnaire. The analysis technique used is multiple linear regression equations with a significance level of 5%. The results show that the use of information technology, learning orientation, and performance have positive and significant effects on competitive advantage in the SMEs of Pottery Kasongan, Bantul Regency. The use of information technology and learning orientation have positive and significant effects on the performance of the Small and Medium Enterprises (MSME) Gerabah Kasongan, Bantul Regency. On the other hand, performance can mediate the effect of the use of information technology and learning orientation on the competitive advantage.